Microstructural and chemical characterization of a purple pigment from a Faiyum mummy portrait. Issue 1 (19th November 2020) - Gates, Glenn; Wu, Yaqiao; Burns, Jatuporn; Watkins, Jennifer; Butt, Darryl P.
Abstract: Results are presented from analyses that were conducted to explain the presence of chromium, detected noninvasively using energy‐dispersive X‐ray fluorescence (XRF), in the unusually large (2‐3mm diameter) rough gem‐like purple pigment particles in the paint used for a Faiyum mummy portrait. An approximately 50 μm diameter particle of the chromium‐containing purple pigment was extracted from the Portrait of a Bearded Man, dated to Roman Imperial Egypt in the second century, circa 170‐180 CE, accession #32.6 in the Walters Art Museum collection. The particle was characterized using energy‐dispersive X‐ray fluorescence analysis, electron microscopy, diffraction, and atom probe tomography. It is demonstrated that the purple pigment particle is a heterogeneous organic pigment, specifically, a lake pigment likely derived from either plant or insect matter, which contains minor percentages of both transition metals and alkali / alkali earth metals, with nanometer‐scale crystallites of lead carbonates and sulfates. The analyses revealed for the first time the nanoscale microstructure and stratigraphy in an ancient lake pigment. Results suggest that similarities with respect to time period and place of production may be developed among unprovenienced Faiyum mummy portraits to help localize workshops or artists, using analyses focused on lake pigments to characterize specifically metal‐based mordants. Abstract : This article presents analyses of an ancient purple pigment, made by affixing an organic dye onto an inorganic substrate to make a lake type of pigment. The results of the analyses are useful to provenience studies of Romano‐Egyptian portraits from the ancient world.